Neuronal exosomes reveal Alzheimer's disease biomarkers in Down syndrome. Issue 5 (15th October 2016) - Hamlett, Eric D.; Goetzl, Edward J.; Ledreux, Aurélie; Vasilevko, Vitaly; Boger, Heather A.; LaRosa, Angela; Clark, David; Carroll, Steven L.; Carmona‐Iragui, María; Fortea, Juan; Mufson, Elliott J.; Sabbagh, Marwan; et al.
Abstract: Introduction: Individuals with Down syndrome (DS) exhibit Alzheimer's disease (AD) neuropathology and dementia early in life. Blood biomarkers of AD neuropathology would be valuable, as non‐AD intellectual disabilities of DS and AD dementia overlap clinically. We hypothesized that elevations of amyloid β (Aβ) peptides and phosphorylated‐tau in neuronal exosomes may document preclinical AD. Methods: AD neuropathogenic proteins Aβ1–42, P‐T181‐tau, and P‐S396‐tau were quantified by enzyme‐linked immunosorbent assays in extracts of neuronal exosomes purified from blood of individuals with DS and age‐matched controls. Results: Neuronal exosome levels of Aβ1–42, P‐T181‐tau, and P‐S396‐tau were significantly elevated in individuals with DS compared with age‐matched controls at all ages beginning in childhood. No significant gender differences were observed. Discussion: These early increases in Aβ1–42, P‐T181‐tau, and P‐S396‐tau in individuals with DS may provide a basis for early intervention as targeted treatments become available.